2019
DOI: 10.1371/journal.pone.0221806
|View full text |Cite
|
Sign up to set email alerts
|

Short-term clinical outcomes of patients admitted with chronic liver disease to selected teaching hospitals in Ethiopia

Abstract: Background Chronic liver disease (CLD) is a progressive destruction of liver tissue with subsequent necrosis that persists for at least 6 months. In Ethiopia, despite the high burden report, data on CLD is limited. The objective of this study was to assess short-term clinical outcomes in patients admitted with chronic liver disease to three tertiary teaching hospitals in Ethiopia and to identify predictors of mortality. Methods A cohort of 109 patients admitted with CLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 24 publications
3
17
1
Order By: Relevance
“…Hepatic encephalopathy (32.8%), ascites (20.4%), hepatocellular carcinoma (19.9%), and infections (18.8%) were prevalent in a large proportion of hospitalized patients. These are similar to other studies that have been conducted on this subject but in variable proportions [ 7 , 35 ]. Early identification of the following complications and their precipitating factors can help reduce the rate of admissions or death in these patients.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Hepatic encephalopathy (32.8%), ascites (20.4%), hepatocellular carcinoma (19.9%), and infections (18.8%) were prevalent in a large proportion of hospitalized patients. These are similar to other studies that have been conducted on this subject but in variable proportions [ 7 , 35 ]. Early identification of the following complications and their precipitating factors can help reduce the rate of admissions or death in these patients.…”
Section: Discussionsupporting
confidence: 90%
“…The male predominance of 2:1 reported in this study parallels that reported by Achinge et al in Nigeria [27]. Other reports from studies conducted in sub-Saharan Africa and other western countries have shown comparable male predominance [7,26]. A possible reason for this is that men are involved in events that exposes them to risk factors that causes…”
Section: Plos Onesupporting
confidence: 87%
See 3 more Smart Citations